Casein phosphopeptide combined with fluoride enhances the inhibitory effect on initial adhesion of Streptococcus mutans to the saliva-coated hydroxyapatite disc - Xiaodie Wang; Limin Liu; Xiaoyan Zhou; Yongbiao Huo; Jinlong Gao; Haijing Gu (BMC, 2020)
Abstract Background Recent preventive strategies for dental caries focus on targeting the mechanisms underlying biofilm formation, including the inhibition of bacterial adhesion. A promising approach to prevent bacterial adhesion is to modify the composition of acquired salivary pellicle. This in vitro study investigated the effect and possible underlying mechanism of pellicle modification by casein phosphopeptide (CPP) on Streptococcus mutans (S. mutans) initial adhesion, and the impact of fluoride on the efficacy of CPP. Methods The salivary pellicle-coated hydroxyapatite (s-HA) discs were treated with phosphate buffered saline (negative control), heat-inactivated 2.5% CPP (heat-inactivated CPP), 2.5% CPP (CPP) or 2.5% CPP supplemented with 900 ppm fluoride (CPP + F). After cultivation of S. mutans for 30 min and 2 h, the adherent bacteria were visualized by scanning electron microscopy (SEM) and quantitatively evaluated using the plate count method. Confocal laser scanning microscopy (CLSM) was used to evaluate the proportions of total and dead S. mutans. The concentrations of total, free, and bound calcium and fluoride in the CPP and fluoride-doped CPP solutions were determined. The water contact angle and zeta potential of s-HA with and without modification were measured. The data were statistically analyzed using one-way ANOVA followed by a Turkey post hoc multiple comparison test. Results Compared to the negative control group, the amount of adherent S. mutans significantly reduced in the CPP and CPP + F groups, and was lowest in the CPP + F group. CLSM analysis showed that there was no statistically significant difference in the proportion of dead S. mutans between the four groups. Water contact angle and zeta potential of s-HA surface significantly decreased in the CPP and CPP + F groups as compared to the negative control group, and both were lowest in the CPP + F group. Conclusions Pellicle modification by CPP inhibited S. mutans initial adhesion to s-HA, possibly by reducing hydrophobicity and negative charge of the s-HA surface, and incorporating fluoride into CPP further enhanced the anti-adhesion effect.